Manipulating the wild: a survey of restoration and management interventions in U.S. wilderness. Issue 5 (18th January 2018) - Lieberman, Lucy; Hahn, Beth; Landres, Peter
Abstract : Landscape scale restoration is a common management intervention used around the world to combat ecological degradation. For wilderness managers in the United States, the decision to intervene is complicated by the Wilderness Act's legal mandate to preserve wilderness character and demonstrate managerial restraint (16 U.S.C. § 1131–1136). We assessed the frequency and type of management interventions, specifically actions to manage ecosystems, that have occurred in the National Wilderness Preservation System between 2011 and 2015, including the specific type of intervention, the methods used, the project proponent, and the factors that influenced the decision to act. We sent an online survey to staff members at 527 wilderness units from four federal agencies that manage wilderness and found that management interventions occurred in 37% of wildernesses sampled ( n = 210). The greatest frequency of interventions occurred in the National Park Service (75%), and the three most common interventions were vegetation treatments (46%), wildfire (35%), and wildlife restoration projects (18%). Our findings point to a need for greater transparency about information on management interventions. We recommend creating an interagency database to track information on management interventions in wilderness to better understand which actions are occurring and why; such a database could help inform wilderness stewardship decisions while demonstrating best practices for ecological restorations implemented within the constraints of the Wilderness Act.